A COMPARATIVE STUDY OF CLINICAL EFFECT OF HYPERBARIC BUPIVACAINE WITH FENTANYL VS HYPERBARIC LEVOBUPIVACAINE WITH FENTANYL FOR SPINAL ANAESTHESIA IN ADULT PATIENTS UNDERGOING ELECTIVE LOWER LIMB SURGERIES - TEJINDERPAL KAUR GREWAL; BALWINDER REKHI; TANVEER SINGH KUNDRA; PARMOD KUMAR; PRANSHU RANI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The aim of the present study was to compare the safety and efficacy of 2.5 ml of 0.5 % hyperbaric bupivacaine with 25 mcg of fentanyl and 2.5 ml of 0.5 hyperbaric levobupivacaine with 25 mcg fentanyl when given intrathecally in adult patients undergoing elective lower limb surgeries. Methods: Our study was carried out in the Department of Anaesthesiology & Intensive Care, Rajindra hospital attached to Government Medical College Patiala from Jan 2023 to Jan 2024. The study was conducted on 100 patients and randomly divided into two groups with 50 patients in each group. Results: There was no significant difference in the age, sex and weight distribution of the patients between the groups. The baseline data in both the groups was not statistically significant. In group I, Incidence of hypotension was 44% while it was 8% in group II and Incidence of bradycardia in group I was 48% while it was 8% in group II. Thus the difference between incidence of hypotension and bradycardia was found statisticallly significant as p value is <0.05. In group I, Mean time to onset of sensory block was 2.72±0.08 minutes while it was 2.76±0.08 minutes in group II which was statistically nonsignificant as p value was >0.05. In group I, Mean Duration of sensory block was 247.90±24.12 minutes while it was 311.18±15.57 minutes in group II which was statistically highly significant as p value was <0.001. In group I, Mean time to onset of motor block was 1.60±1.18 minutes while it was 2.27±0.064 minutes in group II which was statistically highly significant as p value is <0.001. In group I , Mean duration of motor block was 144.32±18.48 minutes while it was 112.04±12.15 minutes in group II which was statistically highly significant as p value was <0.001.The mean bromage scale at different intervals in group I and group II intraoperatively showed statistically significant results. Conclusion: We concluded that in Lower limb surgeries, combination of levobupivacaine and fentanyl decreases the incidence of adverse effects such as hypotension and bradycardia, provides a better hemodynamic stability and offers shorter block time thus minimizing the risk and providing early mobility. Therefore, the combination of levobupivacaine with fentanyl could be preferred combination for lower limb surgeries.